Exploring The Impacts of Technological Disruption on Financial Performance and Business Sustainability: A Case Study of PT Jasa Marga Tollroad Operator (JMTO) - Muhammad Aldi Wicaksono; Eka Pria Anas (Syntax Corporation, 2022)
The rapid development of technology in recent years has disrupted economic and business activities in all sectors of the world, thus becoming a challenge and threat to companies in maintaining their business continuity and financial performance. Companies face the risk of financial distress if they cannot adapt quickly to changing conditions. This study aims to analyze the impact of technological disruption on corporate financial performance and business sustainability. A case study was conducted on the toll road operators in Indonesia, namely PT Jasamarga Tollroad Operator (JMTO), which is facing a disruptive situation due to changes in technology and toll transaction policies in Indonesia. This research uses a qualitative descriptive case study approach to analyze the company's business model and Strategy. It uses a quantitative method by calculating financial projections and measuring company performance using financial ratios. The results of the study show that the company's financial performance has decreased significantly and can potentially be exposed to financial distress if management does not have an effective adaptation strategy in dealing with technological disruptions. This contributes to providing an overview of the impact of technological disruption on the company's performance and business continuity, thus encouraging company management to develop an effective adaptation strategy plan in dealing with various changes.